EFEKTIFITAS PELAYANAN PUSKESMAS SEBAGAI FASILITAS KESEHATAN PERTAMA DALAM PROGRAM BPJS DI PUSKESMAS KARAWACI BARU - Sutoro Sutoro; Dodi Subagia; Doddy Mulyono (Gapenas Publisher, 2023)
This study aims to determine the Effectiveness of Puskesmas Services as the First Health Facility in the BPJS Program at the Karawaci Baru Health Center, Tangerang City. The type of research used is qualitative with descriptive type and uses primary and secondary data sources by determining informants using a purposive sampling technique of 5 (five) people then data is collected using observation, interview and documentation techniques after that it is analyzed using data reduction techniques, presentation data and drawing conclusions as well as the validity of the data using triangulation techniques. The results of the study show that in terms of service quality it can be said that it is still not good. This shows that the existing facilities are still very much needed, in order to provide quality services to the community. Good productivity from sufficient medical equipment and health workers have good skills which can be seen in terms of officer discipline, clarity of responsible officers, timeliness and fast action. Morale is meaningful between the provision of incentives and morale, if the provision of incentives is fulfilled it will be able to encourage the morale of health workers in carrying out their duties because the level of morale possessed by a person can be judged from what is achieved and what is desired. The flexibility of adaptation that exists between officers and patients is considered to have fulfilled what was needed at that time, namely to be noticed by officers both during treatment in the room and while they were waiting